Centenarians as extreme phenotypes: An ecological perspective to get insight into the relationship between the genetics of longevity and age-associated diseases. (July 2017) - Giuliani, Cristina; Pirazzini, Chiara; Delledonne, Massimo; Xumerle, Luciano; Descombes, Patrick; Marquis, Julien; Mengozzi, Giacomo; Monti, Daniela; Bellizzi, Dina; Passarino, Giuseppe; Luiselli, Donata; Franceschi, Claudio; et al.
Highlights: The identification of genes that promote longevity and those that protect from diseases depends upon environment interactions, as the same variants could be protective, neutral, or risk according to environmental changes (internal or external). The approach of "extreme phenotypes" reduces the heterogeneity of the phenotype and could lead to more robust associations. The model of centenarians can be crucial to interpret the biological meaning of disease variants identified in association (case–control) studies on age-related pathologies. Genetic risk factors need to be interpreted considering population genetic variability and past selective pressures that have shaped genomic background of the populations. Abstract: In this review, we address the genetic continuum between aging and age-related diseases, with particular attention to the ecological perspective. We describe the connections between genes that promote longevity and genes associated with age-related diseases considering tradeoff mechanisms in which the same genetic variants could have different effects according to the tissue considered and could be involved in several biological pathways. Then we describe mechanisms of antagonistic pleiotropy, focusing on the complex interplay between genetic variants and environmental changes (internal or external). We sustain the use of centenarians as "super-controls" for the study of the major age-related diseases, starting from the concept that the maximization of the phenotypic differences in the considered cohort, achieved by selecting the most divergent phenotypes, could be useful for increasing the significant differences observed in the genetic association study. We describe the potential impact of the population genetic variability in the study of human longevity and the possible contribution of the past selective pressures in shaping the current genomic background of individuals. In conclusion, we illustrate recent findings emerged from whole-genome sequencing of long-lived individuals and future perspectives for interpreting the huge amount of genetic data that will be generated in the next future.